Ventilator-associated pneumonia prevention: one good turn does not always deserve another - Póvoa, P. (2017)
Funding: This work was supported by the Calouste Gulbenkian Foundation, Gulbenkian Professorship 121986/2012; the Foundation for Science and Technology through the grant ANR/BEX-BID/0153/2012, contract IF/00951/2012 (to SSL), fellowship PD/BD/52420/2013 (to RJ) and travel ship SFRH/BSAB/114291/2016 (to JM); iNOVA4Health Research Unit, LISBOA-01-0145-FEDER-007344.